O manejo transferencial em freud: Uma análise da relação entre transferência e sugestão - Ferreira, Diego Diz; Carrijo, Christiane [UNESP] (FapUNIFESP (SciELO), 2016)
This article intends to elucidate the relationship between transference and suggestion taking Freud's production from the first and second decade as the reference, highlighting the work on psychoanalytic technique. The aim is to reveal how the management of transference would prevent the psychoanalytic clinical method from having its eficacy reduced by suggestion. From the category of transference neurosis, it is possible to think of epistemological strategies to respond to the criticisms from other areas of knowledge, which claim that psychoanalysis is a therapy that has its effectiveness guaranteed due to the phenomenon of client suggestibility faced with the figure of the analyst.
Transference management in Freud: An analysis of the relationship between transference and suggestion
Keywords: Clinic; Epistemology; Psychoanalysis; Suggestion; Transference